The Use of Methylene Blue during Liver Transplantation for Vasoplegia. (23rd June 2021) - Harding, Paul; Nicholas, Thomas; Kassel, Cale
Abstract : The use of methylene blue for vasoplegia in cardiac cases with cardiopulmonary bypass, septic shock, and acute liver failure is well documented. Use of MB for liver transplantation has been largely limited to case reports. We describe three separate liver transplantation patients with significant hypotension following reperfusion. Administration of methylene blue to each patient resulted in a significant decrease in vasopressor medication and two patients weaned completely. We argue that the use of MB should be considered as a treatment option for refractory hypotension.